Kewajiban pada Perkawinan “Pada Gelahang” dalam Perspektif Hukum Adat Bali - Putu Dyatmikawati (Jurnal Kajian Bali (Journal of Bali Studies))
Pada Gelahang marriage is relatively a new form of marriage in traditional community (desa pakraman) in Bali. Commonly the recognized form of marriage is biasa (common) marriage (the wife left her house and joined her husband’s family) and nyentana marriage (the husband left his house and joined his wife’s family). This is the consequence of kapurusa kinship system (patrilineal) in traditional community in Bali. The form of Pada Gelahang marriage was chosen for those who could not hold biasa marriage and nyentana marriage, as each bride and groom was born as the only child in their family. Based on the results of the research, there were found that the numbers of couples who had held pada gelahang marriage were increasing year to year. Based on Balinese customary law, the couples of pada gelahang marriage conduct their responsibilities in two places (double), namely the responsibilities to the family and to her husband’s traditional village, as well the responsibilities to the family and to his wife’s traditional village.